Two new species of the Rhyacophila anatina Species Group from China (Trichoptera: Rhyacophilidae) - Sun, Changhai (Zootaxa, 2016)
Two new species of the Rhyacophila anatina Species Group, R. coalita n. sp. and R. bicaudata n. sp. are described, diagnosed and illustrated. Rhyacophila coalita n. sp. is somewhat similar to R. yipung Schmid and R. elongata Kimmins in the male genitalia, but can be distinguished from them by the deep incision at the apex of the dorsal process of the aedeagus, fused anal sclerites, and a pair of membranous bulbs at the middle of the aedeagus. Rhyacophila bicaudata n. sp. is similar to R. triangularis Schmid in male genitalia, but can be diagnosed by the longer preanal appendages, the slightly incised posteroventral margins of preanal appendages, and a gradually narrowed apicodorsal lobe of segment IX.